Outcomes and Pattern of Bimalleolar Ankle Fracture in Adults: A Cross-Sectional Study: Outcomes and Pattern of Bimalleolar Ankle Fracture in Adults - Lakhani, Sartaj; Hussain Bhatti, Sajjad; Ali Jatoi, Zulfiqar; Shuaib Chandio, Muhammad; ullah, Aziz; Rahman Khan, Abdul; Keerio, Niaz Hussain (Pakistan Journal of Health Sciences, 2022)
A total of 10% of all bone fractures are found in the ankle, making it the most often broken bone in the body. Objective: To assess the outcome and the pattern of bimalleolar ankle fractures in adults. Methods: A total of 72 individuals with bimalleolar ankle fractures were recruited in this study and followed up for a total of 12 weeks. An evaluation of the results after 12 weeks was done using the American Orthopedic Foot and Ankle Score & the Visual Analog Pain Scale. The amount of discomfort, functional ability, and alignment were the three key indicators of the results. Results: The average age of the patients was 36.4 10.4 years, ranging from 19 to 60 years. There were 3:2 more men than women. Half of the fractures were due to falls, 36.1% by automobile accidents, and 13.9% by motorcycle accidents. Of the cases, 63.9 percent included closed fractures. According to the Weber classification, B and C fractures were the most frequent, occurring in 33 (45.8%) and 31 (43.1%) individuals, respectively. The mean AOFAS at three months was 78.2. Between 1 and 3, the VAS was 43.1%. 38.8% of the patients, or 28, reported no discomfort. Conclusions: Patients tended to be young in this study. Delaying final care for up to a week after a fracture does not seem to have a negative impact on the result. The medial clean space (less than 4mm) was the primary indicator of a successful result.